Use of Spectroscopic Techniques to Monitor Changes in Food Quality during Application of Natural Preservatives: A Review - Hassoun, Abdo; Carpena, Maria; Prieto, Miguel A.; Simal-Gandara, Jesus; Ozogul, Fatih; Ozogul, Yesim; Regenstein, Joe M. (Mdpi, 2020)
Consumer demand for food of high quality has driven research for alternative methods of food preservation on the one hand, and the development of new and rapid quality assessment techniques on the other hand. Recently, there has been a growing need and interest in healthier food products, which has led to an increased interest in natural preservatives, such as essential oils, plant extracts, and edible films and coatings. Several studies have shown the potential of using biopreservation, natural antimicrobials, and antioxidant agents in place of other processing and preservation techniques (e.g., thermal and non-thermal treatments, freezing, or synthetic chemicals). Changes in food quality induced by the application of natural preservatives have been commonly evaluated using a range of traditional methods, including microbiology, sensory, and physicochemical measurements. Several spectroscopic techniques have been proposed as promising alternatives to the traditional time-consuming and destructive methods. This review will provide an overview of recent studies and highlight the potential of spectroscopic techniques to evaluate quality changes in food products following the application of natural preservatives.
Keywords: essential oils; fluorescence; UV-Vis spectroscopy; Fourier transform infrared; Raman; edible films; shelf-life; antioxidant; antimicrobial